2022
DOI: 10.1155/2022/5374262
|View full text |Cite
|
Sign up to set email alerts
|

TWIST1-EP300 Expedites Gastric Cancer Cell Resistance to Apatinib by Activating the Expression of COL1A2

Abstract: The association between collagen type I alpha (COL1A) and chemoresistance has been verified in cancers. However, the specific role of COL1A2 in gastric cancer (GC) cell resistance to apatinib, a highly selective small-molecule inhibitor of vascular endothelial growth factor receptor 2, has not been investigated before. The purpose of this study was to explore the potential factors associated with COL1A2 regulation on GC cell apatinib resistance in vitro. With the aid of the Oncomine database and integrated bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…[ 41 ] COL1A2 was regulated by TWIST1-EP300 and LncRNA LIFR-AS1/miR-29a-3p axis thus contribute to apatinib resistance and GC progress. [ 42 , 43 ] COL1A2 also promoted BGC-823 and SGC-7901 apoptosis through the PI3k-Akt signaling pathway. [ 44 ] As for PDGFRB, it is showed that PDGFRB favored migration invasion and proliferation and CSC characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…[ 41 ] COL1A2 was regulated by TWIST1-EP300 and LncRNA LIFR-AS1/miR-29a-3p axis thus contribute to apatinib resistance and GC progress. [ 42 , 43 ] COL1A2 also promoted BGC-823 and SGC-7901 apoptosis through the PI3k-Akt signaling pathway. [ 44 ] As for PDGFRB, it is showed that PDGFRB favored migration invasion and proliferation and CSC characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Transcription factor enrichment analysis shows that they are mainly enriched in EP300, MAX, ESR1, ERG, BRD4, MYC, FOXA1, HIF1A, RUNX1, CTCF and other transcription factors. These transcription factors play an important role in the progression of gastric cancer, such as EP300 has the ability to regulate the expression of COL1A2 to control the drug resistance of gastric cancer cells to Apatinib (47). BRD4 activates C-MYC through transcriptional and epigenetic regulation, which increases the proliferation of gastric cancer cells and inhibits the apoptosis of gastric cancer cells(48).…”
Section: Discussionmentioning
confidence: 99%
“…Transcription factor enrichment analysis showed that they were mainly enriched in EP300, MAX, ESR1, ERG, BRD4, MYC, FOXA1, HIF1A, RUNX1, CTCF and other transcription factors. These transcription factors play an important role in the progression of GC; for example, EP300 has the ability to regulate the expression of COL1A2 to control the drug resistance of gastric cancer cells to apatinib [47]. BRD4 activates C-MYC through transcriptional and epigenetic regulation, which increases the proliferation of gastric cancer cells and inhibits the apoptosis of gastric cancer cells [48].…”
Section: Discussionmentioning
confidence: 99%